2020
DOI: 10.1002/ccd.28744
|View full text |Cite
|
Sign up to set email alerts
|

Chronic total occlusion percutaneous coronary intervention in Latin America

Abstract: Objectives To report clinical, angiographic characteristics, outcomes, and predictors of unsuccessful procedures in patients who underwent chronic total occlusion (CTO) percutaneous coronary interventions (PCI) in Latin America. Background CTO PCI has been increasingly performed worldwide, but there is a lack of information in this region. Methods An international multicenter registry was developed to collect data on CTO PCI performed in centers in Latin America. Patient, angiographic, procedural and outcome d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
(42 reference statements)
2
29
1
1
Order By: Relevance
“…IS‐CTO PCI was defined as a PCI attempt in a coronary segment with prior metallic stent(s) and occlusive stenosis 5 mm proximal or within the stent. Clinical, angiographic, procedural, and postprocedure outcomes used standard definitions from the LATAM CTO registry 9 . In‐hospital major adverse cardiovascular events (MACE) was defined as all‐cause death, myocardial infarction, or stroke.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IS‐CTO PCI was defined as a PCI attempt in a coronary segment with prior metallic stent(s) and occlusive stenosis 5 mm proximal or within the stent. Clinical, angiographic, procedural, and postprocedure outcomes used standard definitions from the LATAM CTO registry 9 . In‐hospital major adverse cardiovascular events (MACE) was defined as all‐cause death, myocardial infarction, or stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical, angiographic, procedural, and postprocedure outcomes used standard definitions from the LATAM CTO registry. 9 In-hospital major adverse cardiovascular events (MACE) was defined as all-cause death, myocardial infarction, or stroke. Myocardial infarction was defined using the universal definition of MI (type 4a MI) (22).…”
Section: Definitionsmentioning
confidence: 99%
“…And second, what is the best way to achieve procedural success with fewer complications? Quadros et al 4 have contributed to the answers, and we hope their efforts continue.…”
mentioning
confidence: 87%
“…An opportune study is published in this issue of the journal by Quadros et al, 4 providing further insight into this matter in the Latin American population. Using the LATAM CTO international registry, the authors analyzed the CTO PCI experience in 1,040 patients who underwent PCI in different Latin American countries, of which 59% were in Brazil.…”
mentioning
confidence: 99%
“…Coronary chronic total occlusion (CTO) percutaneous coronary interventions (PCI) are becoming increasingly performed worldwide with increasing success rates 1,2 . Although the antegrade approach is usually preferred, the retrograde approach is used in about a third of CTO PCI procedures to increase the chance of procedural success 2 . Red flags had been raised to retrograde approach since some studies found increased risk of complications, but this was not consistent across the literature 1 .…”
mentioning
confidence: 99%